Emotion dysregulation and eating disorders—Associations with diagnostic presentation and key symptoms. Issue 8 (21st July 2018) - Monell, Elin; Clinton, David; Birgegård, Andreas
Abstract: Objective: Emotion dysregulation seems involved in the development, maintenance, and outcome of eating disorders (EDs). The present study aimed to differentiate patients with EDs from a comparison group on emotion dysregulation, and to examine emotion dysregulation in relation to ED diagnostic presentation and ED symptoms. Method: Participants, patients with EDs ( N = 999) and a student comparison group ( N = 252), completed the Difficulties in Emotion Regulation Scale and the Eating Disorder Examination Questionnaire. Patients were compared to the comparison group and compared by diagnosis regarding emotion dysregulation, and unique associations between emotion dysregulation aspects and ED symptoms were examined. Results: Patients reported greater general emotion dysregulation than the comparison group, especially poorer emotional awareness and clarity. There were very few diagnostic differences. In both patients and the comparison group, limited access to emotion regulation strategies was associated with cognitive ED symptoms, and presence of binge eating in the comparison group. In patients, poor emotional awareness and emotional non‐acceptance were additionally associated with cognitive symptoms, and difficulties in impulse control and emotional non‐acceptance were associated with binge eating. Discussion: Emotion dysregulation is an important transdiagnostic characteristic of ED. Results suggest interventions that enhance emotional awareness and acceptance, as well as emotion regulation skills training, in both ED treatment and prevention.